Significantly enhanced mechanical quality factor of acceptor-doped quadruple point composition in lead-free Ba(Zr,Ti)O3 ceramics - Yang Yang; Hanbing Zhang; Guanqi Wang; Ying Li; Jiantuo Zhao; Yuanchao Ji; Xiaobing Ren (Journal of Materiomics)
High mechanical quality factor (Qm) is crucial in high-power applications of piezoelectric ceramics because it affects key performance parameters such as sensitivity, efficiency, and stability of devices. Acceptor doping has been the state-of-the-art approach to improve Qm. In the past few decades, many previous research has focused on acceptor doping at the phase boundary to achieve high-performance piezoelectric ceramics. Here, we found that compared with the acceptor-doped phase boundary compositions, the acceptor-doped quadruple point composition can achieve significantly enhanced Qm. The optimal Qm value is up to 1100, which is three times higher than the Qm (approximately 254) obtained in the acceptor-doped phase boundary composition, and also higher than the Qm obtained in the acceptor-doped single-phase region compositions. Piezoresponse force microscopy (PFM) characterization reveals that the pinning effect induced by defect dipoles is more pronounced in the acceptor-doped quadruple point composition compared with the acceptor-doped phase boundary composition, resulting in reduced domain mobility and enhanced Qm. This work provides new insights into the design of lead-free and lead-based piezoelectric materials with high mechanical quality factors.